The Global Impact of Wahhabism: Saudi Arabia's Ideological Expansion and Geopolitical Influence - Parawati, Erina Dwi (Islamic Thought Review, 2024)
This article examines Wahhabism as an Islamic ideological movement that developed from a local religious renewal movement in Najd into a global geopolitical force through the support of the Kingdom of Saudi Arabia. The purpose of the study is to explore the impact of the spread of Wahhabism on the dynamics of politics, society, and foreign policy in various countries, especially in the context of bilateral relations between Saudi Arabia and the countries that are the targets of the spread of the ideology. The study uses a qualitative approach with a literature study method through analysis of primary and secondary sources, including books, journal articles, and policy reports related to Wahhabism and Islamic geopolitics. The results of the study show that the spread of Wahhabism is supported by Saudi Arabia's economic power through oil diplomacy and funding of transnational religious institutions. The main findings reveal that Wahhabism has created complex dynamics in countries, including the emergence of Islamic conservation groups, tensions with moderate local Islamic traditions, and challenges to socio-political integration. Although Saudi Arabia is trying to reform the image of Wahhabism under vision 2030, this ideology remains an important instrument in Saudi foreign policy and shapes the global Islamic geopolitical landscape.